Language and its Role in Bridging International Communication - Georgiana Silvia LEOTESCU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The English language is in a continuous process of advancement as society evolves and people make distance irrelevant by communicating with each other in various ways. It is unquestionable that the development of technology has substantially improved the English language. Not only was it enriched, but it also became the official donner for many languages around the world. Words changed both their meaning and their grammatical category. A simple noun as text became the verb to text with the development of mobile phones. The word “google” started from the name of the search engine and developed into a transitive verb. The name of a company also converted into a verb and even more a concept uberization. Moreover, the association of two basic words such as face and book created a word that began to be used worldwide.